Shipwrecks of flat-bottom vessels used in local transport in the Gulf of Gdańsk from the 16th to the 19th century - Bednarz, Tomasz (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Out of nearly 30 wooden shipwrecks identified and examined at the bottom of the Gulf of Gdańsk, dated back to the 15th–19th centuries, five are flat-bottom vessels presented in this article. They were used to reload goods, transport cargo between the ports within this area, or operated as an inland means of transport for timber floated down the Vistula River. The most interesting vessel is the F53.26 shipwreck, identified as the remains of the 17th-century reloading ship, discovered with its cargo of quern stones and lead ingots. The article also discusses four other flat-bottom wrecks, F53.9, F53.12, F32.9 and F53.20.